Determinan Kinerja Instansi Pemerintah Daerah - Noch, Muhamad Yamin; Bonsapia, Melyanus; Patiran, Andarias; Tuhumury, Harry; Pattiasina, Victor (Public Policy, 2021)
This study examines the Determinants of Performance Factors of Regional Government Agencies in Papua Province. The test was conducted on a sample of 77 respondents. The sample method used is purposive sampling. Data collection is done by direct survey. Hypothesis testing is tested empirically using multiple linear regression. The results of the analysis show that regional financial management has proven to have an effect on the performance of government agencies in the Papua Provincial Government, the Regional Financial Accounting System has no effect on the performance of government agencies in the Papua Provincial Government. governance is proven to have no effect on the performance of government agencies in the Papua Provincial Government and finally Regional financial management, regional financial accounting systems, supervision and good governance are proven to have a positive and significant effect on the performance of government agencies in the Papua Provincial Government.